Expression of a homeobox gene (SIX5) in borderline ovarian tumours. Issue 3 (1st March 2000) - Winchester, C; Robertson, S; MacLeod, T; Johnson, K; Thomas, M
Abstract : Aims —To assess the expression of SIX5 (a homeobox gene) mRNA in surface coelomic epithelium, endocervical epithelium, Fallopian tube epithelium, and benign, borderline, and malignant epithelial ovarian tumours. Methods —10 normal premenopausal ovaries, 10 normal Fallopian tubes, 10 normal cervices, 10 normal postmenopausal ovaries, 10 benign epithelial ovarian tumours, 10 malignant epithelial ovarian tumours, and 40 borderline epithelial ovarian tumours were studied retrospectively. The tissues had been fixed in formalin and embedded in paraffin wax. The tumours had previously been typed into mucinous, serous, or mixed tumours and assigned to the borderline category according to the FIGO/WHO criteria. Expression was assessed by in situ binding of SIX5 specific sense and antisense riboprobes. Hybridisation of the riboprobes was detected using a standard immunohistochemical technique and the results correlated with expression in the normal epithelium of the endocervix, Fallopian tube, surface coelomic epithelium, and ovarian tumours. Results —Expression of SIX5 mRNA was demonstrated in normal Fallopian tube epithelium and normal endocervical epithelium. SIX5 mRNA was not detected in normal ovarian epithelial tissue at any of the times studied during the menstrual cycle. Expression of SIX5 was not shown in benign epithelial ovarian tumours or in any of the malignant epithelial ovarian tumours. In 31 of 37 borderline epithelial ovarian tumours (84%), SIX5 expression was found in the epithelial cells. Conclusions —SIX5 expression is present in the normal epithelium throughout most of the female reproductive tract, suggesting it may have a role in maintaining epithelial differentiation in these tissues. SIX5 expression appears to be restricted to borderline epithelial ovarian tumours and may be a marker of epithelial differentiation in these tumours; thus borderline ovarian tumours may not be part of a continuum of disease between benign and malignant epithelial ovarian tumours. Further investigation of expression of SIX5 may clarify the molecular processes that promote differentiation of the ovarian surface epithelium.